The Portuguese contribution to the creation of the Falintil–Defence Forces of East Timor (Journal of the Spanish Institute for Strategic Studies, 2018)
In the year 2000, as a result of the process of state-building in the postconflictsituation in East Timor and with the support of internationaldonors, the Transitional Administration of the United Nations agreedto create the Falintil-East Timor Defence Forces constituted from theArmed Forces of Liberation and Independence of East Timor. This paperseeks to reflect on Portugal’s contributions to this process of transformationand development which took place between 2000 and 2016.It maintains that foreign Portuguese policy has supported the statebuildingprocess in East Timor, essentially in the domain of defence, byestablishing mutual Military Cooperation agreements.
Keywords: East-Timor; Portugal; Falintil; Falintil- East Timor Defence Forces; Military Cooperation